2022
DOI: 10.1038/s41598-022-17827-3
|View full text |Cite
|
Sign up to set email alerts
|

ID1 marks the tumorigenesis of pancreatic ductal adenocarcinoma in mouse and human

Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) is a deadly disease that has an increasing death rate but no effective treatment to now. Although biological and immunological hallmarks of PDAC have been frequently reported recently, early detection and the particularly aggressive biological features are the major challenges remaining unclear. In the current study, we retrieved multiple scRNA-seq datasets and illustrated the genetic programs of PDAC development in genetically modified mouse models. Notably, the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…The tumorigenic func�on(s) of ID proteins in many cancers is well established 32 . Studies from our lab and others have clearly demonstrated that ID proteins play a pathogenic role in PDAC 6,7,9,10 . We and others have also shown that knockdown of ID1 or ID3 decrease PDAC cell viability 6,10 .…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The tumorigenic func�on(s) of ID proteins in many cancers is well established 32 . Studies from our lab and others have clearly demonstrated that ID proteins play a pathogenic role in PDAC 6,7,9,10 . We and others have also shown that knockdown of ID1 or ID3 decrease PDAC cell viability 6,10 .…”
Section: Discussionmentioning
confidence: 64%
“…The tumorigenic function of ID proteins is well established in many cancers 32,33 . In PDAC, studies from our lab and others have clearly demonstrated that ID proteins play a pathogenic role and that knockdown of ID1 or ID3 decreases PDAC tumorigenicity 6,7,9,10 . Our previous work showed that ID1 and ID3 bind to and inhibit the activity of the bHLH transcription factor E47, a splice variant of the E2A / TCF3 gene.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Later Id1 repression is also thought to be pSmad3 dependent through activation of ATF3 , that then represses Id1 expression 50 . Id1 over-expression in pancreatic ductal adenocarcinoma in mouse and human is associated with more invasive and undifferentiated cells, a mechanism proposed to be dependent on EIF2 signalling 51 and independent of the TGF-β pathway 52 . Here, we found that SMAD4 mutation in CRC patients was associated with low ID1 mRNA expression and poor survival whereas this association has been also been conflicting 53 .…”
Section: Discussionmentioning
confidence: 99%